Using stratiform magnetic anomalies to map near-surface architecture: insights from the Amadeus Basin. Issue 3 (3rd April 2017) - Austin, J. R.; Schmid, S.; Foss, C. A.
ABSTRACT: The Amadeus Basin displays subtle magnetic anomalies that trace strata for considerable distance, highlighting complex folding patterns. Magnetic modelling techniques can be utilised on these stratiform anomalies to extrapolate the near-surface structure of the basin. However, because of the mathematical trade-off between the dip and magnetisation of bodies, the dips of the bodies cannot be known unless the magnetisation is also known. Normally it would be optimal to measure the magnetisation, but this is not always possible or feasible. In this study, we investigate the relationships between dip and magnetisation using an approach that would generally be considered a little backward, i.e. constraining magnetisation direction using geological data. Three study areas were chosen to investigate a number of stratigraphic horizons, the Waterhouse Range, Glen Helen and Ross River areas. Modelling results suggest that some layers primarily retain induced magnetisation, remanence is dominant in others, but both are present in most. Remanence is mainly associated with relatively oxidised units that contain only hematite (e.g. Arumbera Sandstone), and we have demonstrated that these magnetisations predate folding of the Ross River Syncline. In some cases, the anomalies represent redox zonation within units, e.g. the Pertatataka Formation near Glen Helen, where discrete magnetic layers correspond to thin grey (reduced, magnetite-rich) horizons interbedded with more prevalent red (oxidised, hematite-rich) horizons. We also found that where magnetised units are relatively thin and occur near the surface, their magnetic response is sharp, and in aeromagnetic data such adjacent anomalies commonly overlap to form a single anomaly, thus misrepresenting the magnetic field, and mis-mapping the actual magnetic horizons. While the magnetic properties of the causative bodies are variable, we have demonstrated that a better understanding of the magnetic properties of these magnetised horizons can be used to provide insights into the structure and tectonic history of the Amadeus Basin.